Analysis of the low effectiveness of the Crocodile chemistry lab-assisted PBL model on students' problem-solving abilities and scientific attitudes - Danang Priyadi; Suwardi Suwardi (EDUSAINS, 2025)
This study aims to analyze the effect of the Problem Based Learning (PBL) model assisted by the Crocodile Chemistry Lab (CCL) on students' problem-solving abilities and scientific attitudes in thermochemistry of materials. The research design used is quasi-experimental with a pretest–posttest control group pattern. The research instruments include a problem-solving ability test and a scientific attitude questionnaire that has been expert and empirically validated. The data were analyzed using MANOVA and followed by univariate tests. The research results indicate that the PBL-CCL model has a significant impact on students' problem-solving abilities and scientific attitudes. However, the relatively low partial eta squared values (3.7% and 5.7%) indicate that the model's contribution to the improvement of both variables is still in the small category. Further analysis indicates that the effectiveness of implementation is influenced by students' readiness to learn, variations in motivation, the less-than-optimal implementation of PBL syntax, limitations in equipment facilities, and students' preference for real experiments over digital simulations. This finding confirms that integrating PBL with virtual laboratories has positive potential, but its success is highly influenced by the overall readiness of the learning ecosystem.